Fibroblasts and myofibroblasts in wound healing - Darby IA; Laverdet B; Bonté F; Desmoulière A (Dove Medical Press, 2014)
Ian A Darby,1 Betty Laverdet,2 Frédéric Bonté3, Alexis Desmoulière2 1School of Medical Sciences, RMIT University, Melbourne, VIC, Australia; 2Department of Physiology and EA 6309, FR 3503, Faculties of Medicine and Pharmacy, University of Limoges, Limoges, France; 3LVMH Recherche, Saint Jean de Braye, France Abstract: (Myo)fibroblasts are key players for maintaining skin homeostasis and for orchestrating physiological tissue repair. (Myo)fibroblasts are embedded in a sophisticated extracellular matrix (ECM) that they secrete, and a complex and interactive dialogue exists between (myo)fibroblasts and their microenvironment. In addition to the secretion of the ECM, (myo)fibroblasts, by secreting matrix metalloproteinases and tissue inhibitors of metalloproteinases, are able to remodel this ECM. (Myo)fibroblasts and their microenvironment form an evolving network during tissue repair, with reciprocal actions leading to cell differentiation, proliferation, quiescence, or apoptosis, and actions on growth factor bioavailability by binding, sequestration, and activation. In addition, the (myo)fibroblast phenotype is regulated by mechanical stresses to which they are subjected and thus by mechanical signaling. In pathological situations (excessive scarring or fibrosis), or during aging, this dialogue between the (myo)fibroblasts and their microenvironment may be altered or disrupted, leading to repair defects or to injuries with damaged and/or cosmetic skin alterations such as wrinkle development. The intimate dialogue between the (myo)fibroblasts and their microenvironment therefore represents a fascinating domain that must be better understood in order not only to characterize new therapeutic targets and drugs able to prevent or treat pathological developments but also to interfere with skin alterations observed during normal aging or premature aging induced by a deleterious environment. Keywords: myofibroblast, fibroblast, α-smooth muscle actin, mechanical signaling, fibrosis, scarring